2020
DOI: 10.1016/j.mbs.2020.108452
|View full text |Cite
|
Sign up to set email alerts
|

Could masks curtail the post-lockdown resurgence of COVID-19 in the US?

Abstract: The community lockdown measures implemented in the United States from late March to late May of 2020 resulted in a significant reduction in the community transmission of the COVID-19 pandemic throughout the country. However, a number of US states are currently experiencing an alarming post-lockdown resurgence of the pandemic, triggering fears for a devastating second pandemic wave. We designed a mathematical model for addressing the key question of whether or not the universal use of face masks can halt such r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 33 publications
8
75
0
1
Order By: Relevance
“…The Kermack-McKendrick-type epidemic models are built based on a number of simplifying assumptions, such as (a) a homogeneously-mixed population (i.e., all individuals in the community are assumed to have equal probability of coming in contact with one another), (b) exponentially-distributed waiting time in each epidemiological compartment ( Hethcote, 2000 ; Ngonghala et al., 2020a ; Nishiura & Chowell, 2009 ) and (c) no human demographic processes (i.e., no migration, births or deaths due to causes other than the disease being modeled). The assumption of no human demographic processes (i.e., vital dynamics) stems from the fact that, for a novel disease, such as COVID-19 (where, at the time of introduction, no member of the community has immunity due to natural recovery from prior exposure to the disease or due to immunization), the time scale of the disease is much smaller than the demographic time scale (i.e., the average lifespan of humans in the affected community).…”
Section: Basic Compartmental Epidemic Model For Covid-19 Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kermack-McKendrick-type epidemic models are built based on a number of simplifying assumptions, such as (a) a homogeneously-mixed population (i.e., all individuals in the community are assumed to have equal probability of coming in contact with one another), (b) exponentially-distributed waiting time in each epidemiological compartment ( Hethcote, 2000 ; Ngonghala et al., 2020a ; Nishiura & Chowell, 2009 ) and (c) no human demographic processes (i.e., no migration, births or deaths due to causes other than the disease being modeled). The assumption of no human demographic processes (i.e., vital dynamics) stems from the fact that, for a novel disease, such as COVID-19 (where, at the time of introduction, no member of the community has immunity due to natural recovery from prior exposure to the disease or due to immunization), the time scale of the disease is much smaller than the demographic time scale (i.e., the average lifespan of humans in the affected community).…”
Section: Basic Compartmental Epidemic Model For Covid-19 Transmissionmentioning
confidence: 99%
“…By August 31, 2020, the US has recorded over 6 million confirmed cases and 187, 700 deaths. Although recent modeling data showed that COVID-19 was already spreading in the State of New York by late January 2020 ( Ngonghala et al., 2020a ), the officially reported “index case” for the State was documented on March 1, 2020 (which was traced to a woman who traveled to New York city from Iran, a country that was ravaged by COVID-19 at that time). Starting with the official “index case” on March 1, 2020, the State of New York recorded nearly 70, 000 confirmed cases and about 1, 000 deaths by the end of March 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous work that has considered specific values of testing level and projecting outcomes, our modelling provides all combinations of thresholds for testing and tracing coverage that could prevent a COVID-19 resurgence and a secondary wave whether or not mask were mandatory in secondary schools. Furthermore, previous studies [32][33][34][35][36][37][38][39] have explored the broader impact of masks by simulating lowered transmission across all layers in society. The Covasim model instead has the granularity to consider specific layers, hence allowing our study to specifically explore the impact of mandatory masks in secondary schools, in combination with different levels of TTI coverage.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…A growing number of modelling studies have evaluated the impact of face coverings on the COVID-19 epidemic [32][33][34][35][36][37][38][39]. While the overall message from these models is that, as lockdown measures are relaxed, masks are likely to be effective if they are worn by a large percentage of the population, they often optimistically assumed that a large proportion of transmission events could be prevented with face masks by overestimating their efficacy and guided by evidence of the impact of masks on influenza transmission reduction [15]; hence their results are likely to overestimate impact.…”
Section: Introduction (1262 Words)mentioning
confidence: 99%